The critical review of the pollution haven hypothesis (PHH) - Gill, Fozia Latif; Viswanathan, K. Kuperan; Abdul Karim, Mohd Zaini (EconJournals, 2018)
This paper evaluates the theoretical and empirical basis of the Pollution Haven Hypothesis (PHH) and Porter Hypothesis. The PHH claims that owing to international trade and Foreign Direct Investment (FDI), the developing countries have become the pollution haven for the advanced countries. The Porter Hypothesis portraits an opposite picture than the PHH. According to, the Porter Hypothesis, the FDI in home country induce the induction of more advanced and clean technologies that lead to cleaner environment. In the literature, there is mixed support for these opposing hypotheses. This paper therefore, recommends further rigours research that aims at to find out the true link between trade, FDI and environmental degradation.